A review of features of technology-supported learning environments based on participants' perceptions. (December 2015) - Chang, Hsin-Yi; Wang, Chia-Yu; Lee, Min-Hsien; Wu, Hsin-Kai; Liang, Jyh-Chong; Lee, Silvia W.-Y.; Chiou, Guo-Li; Lo, Hao-Chang; Lin, Jing-Wen; Hsu, Chung-Yuan; Wu, Ying-Tien; Chen, Sufen; et al.
Highlights: We review studies measuring people's perceptions of technology learning environments. A framework conceptualizing technology learning environments (TSLEs) is proposed. It includes six dimensions: technical, content, cognitive, metacognitive, social, & affective. The studies considered more the technical, cognitive and social dimensions. The results provide insights into an overview of the instruments used for TSLEs. Abstract: In this study we reviewed 22 studies on developing instruments that measure teachers', students' and adult students' perceptions of learning environments enhanced by a certain type of technology. We conducted a review of all the instruments to propose a new framework conceptualizing technology-supported learning environments (TSLEs) for future instructional designs, and research on learning environments. This framework was also confirmed with the literature on learning theories. The framework consists of six dimensions: technical, content, cognitive, metacognitive, social, and affective. We found that the studies took more into consideration the technical, cognitive and social dimensions, and less the content, metacognitive, and affective dimensions. Moreover, usability in the technical dimension, relevance in the content dimension, inquiry learning in the cognitive dimension, student autonomy in the metacognitive dimension, and teacher support in the social dimension are the salient features most often investigated in TSLEs. The results provide insights into an overview of the instruments used for TSLEs, implications for the instructional design of TSLEs, and trends in the current and future research on perceptions of TSLEs.